2021
DOI: 10.1007/s13311-021-01126-2
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of AQP4 Improves Blood–Brain Barrier Integrity and Perihematomal Edema Following Intracerebral Hemorrhage

Abstract: In intracerebral hemorrhage (ICH), delayed secondary neural damages largely occur from perihematomal edema (PHE) resulting from the disruption of the blood-brain barrier (BBB). PHE is often considered the principal cause of morbidity and mortality in patients with ICH. Nevertheless, the main cellular mechanism as well as the specific BBB component involved in the formation of PHE after ICH remains elusive. Herein, we evaluated the role of AQP4, a water channel expressed on the astrocytes of the BBB, in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…AQP4 dysfunction in mouse brain tissue leads to impaired water and solute processing and may lead to brain edema or abnormal protein accumulation [ 60 , 61 ]. Although some studies have shown that AQP4 is involved in brain edema after SAH [ 62 ], in recent years, AQP4 knockout has been found to aggravate brain injury after SAH [ 23 ], suggesting the functional diversity and potential neuroprotective effect of AQP4. Our work is the first to show that AQP4 overexpression can reduce SAH-induced AQP4 depolarization, brain parenchymal ferritin content, and neuronal ferroptosis to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQP4 dysfunction in mouse brain tissue leads to impaired water and solute processing and may lead to brain edema or abnormal protein accumulation [ 60 , 61 ]. Although some studies have shown that AQP4 is involved in brain edema after SAH [ 62 ], in recent years, AQP4 knockout has been found to aggravate brain injury after SAH [ 23 ], suggesting the functional diversity and potential neuroprotective effect of AQP4. Our work is the first to show that AQP4 overexpression can reduce SAH-induced AQP4 depolarization, brain parenchymal ferritin content, and neuronal ferroptosis to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that SAH impairs the polarization of astrocyte AQP4 [ 21 ], while AQP4 knockout aggravates SAH-induced brain injury through impairment of the glymphoid system [ 22 ]. In addition, literature studies have shown that upregulation of AQP4 improves blood–brain barrier integrity and perihematomal edema following intracerebral hemorrhage [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, a recent publication has explored the upregulation of AQP4 in a double knock-down mouse model with promising results when rescuing the channel activity by an enhancer. The authors suggest a pivotal role of AQP4 in suppressing oedema formation by maintaining BBB integrity and upregulating TJs [ 141 ].…”
Section: Mechanisms Altering Blood–brain Barrier (Bbb) Functionmentioning
confidence: 99%
“…Recent in vivo research shows that AQP4 expression is reduced around the perihematomal edema (PHE) area after intracerebral hemorrhage. The PHE lesions in AQP4-deficient mice were significantly larger than that in the wild-type mice, which is related to poor survival outcomes ( Jeon et al, 2021 ). This result implies that AQP4 occupies a very important position in the occurrence of cerebral edema ( Nagelhus and Ottersen, 2013 ; Zhang J. et al, 2019 ; Chen et al, 2021 ).…”
Section: Micro Ribonucleic Acid and Aquaporinmentioning
confidence: 99%